(untitled) (Agricultural Engineering, 2017)
Research on the selected population of students with a standardized questionnaire method concerning the use of IT technologies has been carried out since 2008/09. Results for the data from the first and the last year of research (2009 and 2016) for agricultural students were compared. It was reported that students use IT technologies in the process of learning. Majority of students − 94% (2009) and 98% (2016) positively assessed the usefulness of these technologies in the learning process. The Internet was used mainly for communication (respectively in the investigated years 82.5% and 99.1%). Usefulness of the Internet in the process of studying was marked very high - in 2009 it was 51% positive answers and in 2016 − 77%